ANALISIS KEMAMPUAN PENALARAN LOGIS SISWA YANG MEMILIKI GAYA BERPIKIR SEKUENSIAL ABSTRAK DALAM MENYELESAIKAN MASALAH LOGIKA MATEMATIKA KELAS XI SMA NEGERI I TUNGKAL ULU - Hasan Basri Said; Herlina Susanti; Aisyah Aisyah (Universitas Batanghari Jambi, 2017)
Logical reasoning is a reasoning that conforms to logical rules. Therefore logical reasoning corresponds to mathematical logic material that has correlation with logical rules and obtains a conclusion of an information. The thinking style associated with logical reasoning is the abstract sequential thinking style. This research includes the type of qualitative research that uses descriptive qualitative research methodology. This research will be conducted on students in SMA Negeri I Tungkal Ulu. It is described in this research is the logical reasoning ability of students who have abstract sequential thinking style in solving the problem of mathematical logic. The results of the information-testing test designed by Jhon Parks le Tellier in can be three students who have abstract sequential thinking style. From the results obtained valid and it can be concluded that SSA1 has a high logical penalarn ability, and SSA2 has good logical reasoning ability, whereas SSA3 has less reasoning ability.Keywords: Logical Reasoning, Math logic, Sequential Abstract